The ABP Strategy Applied to the Learning of Renewable Energy Sources with Synchronous and Asynchronous Operability - Guevara-saenz de Viteri, Jessica; Naranjo Valencia, Margarita; Delgado- Plaza, Emerita; Peralta-jaramillo, Juan (2019 XIV Latin American Conference on Learning Technologies (LACLO), 2019)
ABP strategy is applied in learning renewable energy sources using: repetition, grouping, inference, deduction, mental investigation, recognition of technical terms, allowing the value processing of use as a participatory discipline in environmental care. The e-book as a means of consultation in synchronic and asynchronic times between teachers and students proposes cultural change and awareness in institutions of higher education; generating support texts with collaborative writing, for group interaction, receiving inputs to improve the proposed content, the methodological strategy is used as the driving axis in the processlearning.